2021
DOI: 10.1021/acs.energyfuels.1c02138
|View full text |Cite
|
Sign up to set email alerts
|

Structure Design and Performance of the Graphite/Silicon/Carbon Nanotubes/Carbon (GSCC) Composite as the Anode of a Li-Ion Battery

Abstract: Silicon (Si) or Si-based compounds have been paid much attention in the field of lithium-ion battery anodes on account of desirable theoretical capacity, moderate working voltage, abundant resources, and bing nontoxic. However, some disadvantages, including inferior electrical conductivity and enormous volume change in the process of lithiation/delithiation, hinder their widespread application in commercial lithium-ion batteries. To solve the above problems, we designed and prepared the graphite/silicon/carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
(81 reference statements)
0
10
0
Order By: Relevance
“…At the same time, the TG curve of NP-Si@C was measured in an air atmosphere, which was used to calculate the content of pyrolytic carbon contents in NP-Si@C. As shown in Figure b, the weight of NP-Si@C drops sharply between 510 and 620 °C, during which the pitch pyrolytic carbon almost completely oxidized. As the temperature continues to increase, the thermogravimetric curve appears to rise, which may be related to the oxidation of Si at high temperatures. , Therefore, it can be calculated that the weight ratio of pitch pyrolytic carbon in the NP-Si@C composite is about 4.32%. Combined with HR-TEM (Figure d), it can be further concluded that the pitch pyrolytic carbon layer in NP-Si@C is thin and the weight proportion is extraordinarily small.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the TG curve of NP-Si@C was measured in an air atmosphere, which was used to calculate the content of pyrolytic carbon contents in NP-Si@C. As shown in Figure b, the weight of NP-Si@C drops sharply between 510 and 620 °C, during which the pitch pyrolytic carbon almost completely oxidized. As the temperature continues to increase, the thermogravimetric curve appears to rise, which may be related to the oxidation of Si at high temperatures. , Therefore, it can be calculated that the weight ratio of pitch pyrolytic carbon in the NP-Si@C composite is about 4.32%. Combined with HR-TEM (Figure d), it can be further concluded that the pitch pyrolytic carbon layer in NP-Si@C is thin and the weight proportion is extraordinarily small.…”
Section: Resultsmentioning
confidence: 99%
“…As the temperature continues to increase, the thermogravimetric curve appears to rise, which may be related to the oxidation of Si at high temperatures. 37,38 Therefore, it can be calculated that the weight ratio of pitch pyrolytic carbon in the NP-Si@C composite is about 4.32%. Combined with HR-TEM (Figure 3d), it can be further concluded that the pitch pyrolytic carbon layer in NP-Si@C is thin and the weight proportion is extraordinarily small.…”
Section: Resultsmentioning
confidence: 99%
“…The most popular ion batteries on the market are still rocking‐chair LIBs, which have the advantages of rechargeability, lightweight, high operating voltage, low self‐discharge, small voltage hysteresis, low irreversibility, high energy density, cycle life, and so on [69–73] . During the charging process of LIBs, the cathode (mainly Li‐rich materials, such as LiCoO 2 , LiMn 2 O 4 , or LiFePO 4 ) loses electrons (e) in an oxidation reaction, releasing Li + , which moves toward the anode and forms a compound with the anode (usually graphite) electrochemically active material to complete the charging process [74–76] .…”
Section: Overview Of Ion Batteriesmentioning
confidence: 99%
“…The most popular ion batteries on the market are still rockingchair LIBs, which have the advantages of rechargeability, lightweight, high operating voltage, low self-discharge, small voltage hysteresis, low irreversibility, high energy density, cycle life, and so on. [69][70][71][72][73] During the charging process of LIBs, the cathode (mainly Li-rich materials, such as LiCoO 2 , LiMn 2 O 4 , or LiFePO 4 ) loses electrons (e) in an oxidation reaction, releasing Li + , which moves toward the anode and forms a compound with the anode (usually graphite) electrochemically active material to complete the charging process. [74][75][76] The discharge process is the reverse reaction of the charging process: the anode compound loses electrons and releases lithium ions, which move to the vicinity of the positive electrode and re-insert into the positive electrode material to complete the discharge process.…”
Section: Working Principle Of Ion Batteriesmentioning
confidence: 99%
“…To meet the ever increasing demands of portable electronics requirement for higher energy and power densities, high-performance materials development is imperative for lithium-ion batteries (LIBs). Silicon anode materials show the brightest future owing to their super high theoretical capacity (4200 mAh g –1 for Li 22 Si 5 ), relatively low discharge potential (∼0.4 V versus Li + /Li), and rich abundance in the earth. Nevertheless, the commercial application of silicon anode materials is still hindered with the challenges related to the huge volume expansion. The solid electrolyte interface (SEI) and electrode structure are damaged due to tremendous volume change of silicon anode materials during Li + lithiation and delithiation processes, which seriously deteriorate the lifespan of the lithium-ion battery. Various strategies have been adopted to ameliorate these issues, such as controlling the morphology of silicon anode materials, using late-model electrode structures, and employing high-performance binders. …”
Section: Introductionmentioning
confidence: 99%